2011
DOI: 10.1136/thoraxjnl-2011-200650
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial antibody responses associated with the development of asthma in house dust mite-sensitised and non-sensitised children

Abstract: Background Infants who develop house dust mite (HDM) allergy and HDM-sensitised children with severe persistent asthma have low antibody responses to the P6 antigen of Haemophilus influenzae. Objective To measure the development of antibody to two ubiquitous bacteria of the respiratory mucosa in a prospective birth cohort at high risk of allergic disease and to assess which responses are associated with asthma and atopy. Methods IgG1 and IgG4 antibody to H influenzae (P4 and P6) and Streptoccocus pneumoniae (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 36 publications
2
41
1
Order By: Relevance
“…Children with house-dust mite (HDM) sensitization had lower pneumococcal surface protein A titers at three years of age as well as lower anti-P6 antibody for H. influenza 16 and lower pneumococcal antibody titers. 30,39 We recently reported that HDM-stimulated IL-5 secretion was inversely correlated with pneumococcal antibody values in asthmatics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with house-dust mite (HDM) sensitization had lower pneumococcal surface protein A titers at three years of age as well as lower anti-P6 antibody for H. influenza 16 and lower pneumococcal antibody titers. 30,39 We recently reported that HDM-stimulated IL-5 secretion was inversely correlated with pneumococcal antibody values in asthmatics.…”
Section: Discussionmentioning
confidence: 99%
“…This concern becomes especially relevant considering asthma has been reported to be associated with an increased risk of microbial infections 12-14 and suboptimal innate 15 and adaptive immune functions. 16-18 Also, a few recent papers demonstrated evidence of waning of pertussis, mumps, and measles vaccine-induced immunity in children and its potential impact on public health. 8, 19,20 Despite the public health concerns over the outbreaks of vaccine preventable diseases in the United States and elsewhere, currently there are scant data about factors influencing waning of vaccine-induced humoral immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant to this possibility, it has recently been demonstrated that infants and schoolchildren with atopic asthma symptoms display aberrant patterns of humoral immunity against common respiratory bacterial pathogens. This includes reduced production of specific IgG 1 antibody levels that are central to bacterial clearance 84,85 and also reduced levels of specific IgE directed against particulate antigens on bacterial pathogens, which are produced in relatively high titers by nonatopic and asymptomatic atopic subjects. 86 Collectively, these findings emphasize the necessity of obtaining an accurate picture at the population level of the full spectrum of bacterial strains that constitute the respiratory tract microbiome and their population dynamics across the age range during which asthma development is most commonly initiated.…”
Section: The Emerging Issue Of the Respiratory Microbiomementioning
confidence: 99%
“…It is therefore relevant to question whether variations in antibacterial host defense mechanisms may also contribute to asthma susceptibility in young children. Preliminary evidence from the CAS birth cohort (134, 136) suggests that the efficiency of immune surveillance for common nasopharyngeal bacterial species during infancy as measured via specific IgG1 antibody titers is inversely related to risk for subsequent development of atopic asthma in children, and this may reflect the role of this antibody in bacterial clearance. Moreover, we have recently reported that Th2-polarized immunity in school children against these bacterial species is protective against expression of asthma symptoms (137).…”
Section: Additional Complexities In Asthma Developmentmentioning
confidence: 99%